Phase transitions in octanethiol-capped Ag nanocluster microfilm assemblies - Ellis, A.; D'Arcy-Galla, J.; Vijayamohanan, K.; Goswami, R.; Ganesan, P. G.; Ryu, C.; Ramanath, G. (Thermochimica Acta, 2005)
We describe phase transitions in microfilm assemblies of octanethiol (OT)-capped 2-4 nm-diameter Ag nanoclusters prepared from solutions with OT/Ag+ ratios of similar to50. Using DSC we observe two melting/crystallization-type reversible phase transitions: one at similar to61 degreesC due to interdigiated unattached octanethiol, and the other at similar to125 degreesC due to the phase comprised of the assembly of OT-capped nanoclusters. Increased thermal fluctuations weaken the inter-chain hydrophobic interactions between interdigitated OT molecules, leading to both phase transitions. The thiolate bond of OT-molecules bound to Ag nanoclusters are more rigid, thereby requiring a higher temperature to increase the flexibility of the alkyl chain of OT, and to melt the nanocluster assembly. The mobility of the nanoclusters in the melt is limited, and morphological features of the original assemblies are retained during recrystallization. No observable mass loss is detected up to similar to180 degreesC, above which OT molecules desorb from the Ag nanoclusters. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: differential thermal analysis; infrared spectroscopy; phase transitions; silver nanoclusters

Negative thermal expansion in silicalite-1 and zirconium silicalite-1 having MFI structure - Bhange, Deu S.; Ramaswamy, V. (Materials Research Bulletin, 2006)
In situ high temperature X-ray diffraction (HTXRD) studies on monoclinic silicalite-1 (S-1, silica polymorph of ZSM-5) and an orthorhombic metallosilicate molecular sieve, zirconium silicalite-1 (ZrS-1) with MFI structure (Si/Zr = 50) have been carried out using a laboratory X-ray diffractometer with an Anton Parr HTK 1600 attachment. While the structure of the S-I collapsed at 1123 K forming alpha-cristobalite. S-1 and ZrS-1 showed a complex thermal expansion behavior in the temperature range 298-1023 K, ZrS-1 was stable. Powder X-ray diffraction (PXRD) data taken in this region have shown strong negative lattice thermal expansion coefficient, alpha(v) = -6.75 x 10(-6) and - 17.92 x 10(-6) K-1 in the temperature range 298-1023 K-1 for S-1 and ZrS-1 samples, respectively. The thermal expansion behavior of S-1 and ZrS-1 is anisotropic, with the relative strength of contraction along a axis is more than that along b and c axes. Three different thermal expansion regions could be identified in the overall temperature range (298-1023 K) studied, corroborating with the three steps of weight loss in the TG curve of ZrS-1 sample. While the region between 298 and 423 K, displays positive thermal expansion coefficient with alpha(v) = 2.647 x 10(-6) and 4.24 x 10(-6) K-1, the second region between 423 and 873 K shows strong negative thermal expansion (NTE) coefficient alpha(v) = -7.602 x 10(-6) and - 15.04 x 10(-6) K-1, respectively, for S-1 and ZrS-1 samples. The region between 873 and 1023 K, shows a very strong NTE coefficient with alpha(v) = - 12.08 x 10(-6) and -45.622 x 10(-6) K-1 for S-1 and ZrS-1, respectively, which is the highest in the whole temperature range studied. NTE seen over a temperature range 298-1023 K could be associated with transverse vibrations of bridging oxygen atoms in the structure which results in an apparent shortening of the Si-O distances. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; phase transitions; Thermal expansion; X-ray diffraction

Thermal stability of mesoporous SBA-15 and Sn-SBA-15 molecular sieves: an in situ HTXRD study - Shah, Pallavi; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
Highly ordered SBA-15 and Sn-SBA-15 mesoporous molecular sieves with Si/Sn = 80, 60, 40 and 10 have been prepared through direct synthesis route under milder acidic conditions, which were used for the in situ high temperature X-ray diffraction (HTXRD) studies in the temperature range 298-1573 K for the first time in the literature. SBA-15 is found to be thermally stable up to 1473 K and appearance of alpha-cristobalite was observed at 1573 K also supported by the thermogravimetric (TG) data. A strong negative thermal expansion was observed on heating from 298 to 1573 K (alpha(a) = -4.3 x 10(-6) K-1). Sit containing samples (Si/Sn = 80 and 60) showed a positive thermal expansion (6.75 x 10(-6) K-1 and 9.04 x 10(-6) K-1, respectively). On the other hand, the samples with Si/Sn = 40 and 10 showed a strong negative thermal expansion (-4.12 x 10(-6) K-1 and -7.56 x 10(-6) K-1) similar to SBA-15. The linear thermal expansion coefficient varied in the order: Si/Sn = 60 > 80 > 40 > 0 > 10. Sn4+ ions exhibit both tetrahedral and octahedral coordination depending upon the location of these ions either on the walls of the silica (Si/Sn = 80 and 60) or in the corona region of the structure (Si/Sn = 40 and 10), respectively. The thermal decomposition of the samples (TG data) is correlated to the thermal expansion behavior (HTXRD data). The decomposition behavior of template ions located within the pores is strongly influenced by the presence of Sn in the framework and a `soft' interaction probably exists between the template ions and the Sn sites. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: HTXRD studies; phase transitions; Sn-SBA-15; TG data; Thermal expansion

Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions